Distribution patterns of fungal taxa and inferred functional traits reflect the non-uniform vertical stratification of soil microhabitats in a coastal pine forest. Issue 11 (20th September 2019) - Kluting, Kerri; Clemmensen, Karina; Jonaitis, Stanislovas; Vasaitis, Rimvydas; Holmström, Sara; Finlay, Roger; Rosling, Anna
ABSTRACT: In boreal systems, soil profiles typically consist of distinct stratified horizons, with organic layers at the surface overlying deeper mineral horizons providing microhabitat variation along a depth gradient, and vertical stratification of fungal communities along such soil profiles is commonly observed. We studied fungal community structure in a coastal pine forest along a gradient of decreasing influence from the coast. In this system, the vertical stratification pattern of soil microhabitats (defined here as organic, mineral with roots and mineral without roots: O, MR and MN, respectively) is non-uniform; organic horizons are sometimes buried under drifting sand dunes. Our results show that soil microhabitats are distinct with respect to physiochemical characteristics, community composition and OTU richness. While community composition was partly related to depth and distance from the coastal forest edge, microhabitat appeared to have the strongest influence. A closer inspection of the OTUs with the highest relative sequence abundance within each microhabitat revealed that microhabitats support functionally distinct fungal communities with respect to trophic mode and growth morphology. These results suggest that in coastal pine forests, variation in soil microhabitats contributes to the high fungal diversity found belowground and may play an important role in optimizing nutrient cycling. Abstract : Soil fungal communities are shaped by microhabitat characteristics, such as organic vs mineral soil and the presence or absence of roots, more so than soil depth.